2010
DOI: 10.1002/chem.201001316
|View full text |Cite
|
Sign up to set email alerts
|

Studies Toward an Ideal Fluorescence Method to Measure Palladium in Functionalized Organic Molecules: Effects of Sodium Borohydride, Temperature, Phosphine Ligand, and Phosphate Ions on Kinetics

Abstract: Residual metals in fine chemicals are currently detected by using inductively coupled plasma mass spectrometry, which requires expensive instrumentation and does not have high-throughput capabilities. Although fluorescent probes can be amenable to high-throughput analyses of metals, the utility of such analyses is limited due to the lack of generality. Herein, we report a significant improvement (≈19-fold) to our previously reported catalysis-based fluorescent probe for palladium. Specifically, we found that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 55 publications
(54 reference statements)
0
33
0
Order By: Relevance
“…The reaction of deallylation using the electron-poor phosphine ligand (TFP; tri-2-furylphosphine) to better generate the coordinatively unsaturated Pd(0) species has indeed been known1617 (see Supplementary Fig. 1c for scheme), but here we discover its utility in physiological conditions.…”
Section: Resultsmentioning
confidence: 76%
“…The reaction of deallylation using the electron-poor phosphine ligand (TFP; tri-2-furylphosphine) to better generate the coordinatively unsaturated Pd(0) species has indeed been known1617 (see Supplementary Fig. 1c for scheme), but here we discover its utility in physiological conditions.…”
Section: Resultsmentioning
confidence: 76%
“…34 Improvements to this detection methodology include the introduction of reducing agents and phosphine ligands in order to increase the catalytic activity of the palladium, which in turn leads to increased sensitivity of the assay. [35][36] Furthermore, a bis-allyl ether derivative of 1 has been very recently reported that can significantly reduce background fluorescence and as such, delivers a >300-fold signal increase within a 5 minute reaction period. 37 Alternative moieties have also been shown to be selective for palladium detection as a propargyl derivative of compound 1 has been shown to be able to monitor palladium accumulation in living systems via fluorescence.…”
Section: Target Catalysismentioning
confidence: 99%
“…The other possibility is that a phosphate ion can act as a ligand for palladium(0). [26] Conclusions An efficient process has been developed for the carbonylation of chloroacetates to afford malonates by using [PdCl 2 (PPh 3 ) 2 ] as a catalyst with the aid of Bu 4 NI in a weakly alkaline buffer. Excellent selectivity (96 %) and yield (93 %) of DEM were obtained if the reaction was performed in anisole with Na 2 HPO 4 as a proton scavenger and Pd black was not generated.…”
Section: Discussionmentioning
confidence: 99%